M-crawler: Crawling Rich Internet Applications Using Menu Meta-model - Choudhary, Suryakant (Université d'Ottawa / University of Ottawa, 2012)
Web applications have come a long way both in terms of adoption to provide information and services and in terms of the technologies to develop them. With the emergence of richer and more advanced technologies such as Ajax, web applications have become more interactive, responsive and user friendly. These applications, often called Rich Internet Applications (RIAs) changed the traditional web applications in two primary ways: Dynamic manipulation of client side state and Asynchronous communication with the server. At the same time, such techniques also introduce new challenges. Among these challenges, an important one is the difficulty of automatically crawling these new applications. Crawling is not only important for indexing the contents but also critical to web application assessment such as testing for security vulnerabilities or accessibility. Traditional crawlers are no longer sufficient for these newer technologies and crawling in RIAs is either inexistent or far from perfect. There is a need for an efficient crawler for web applications developed using these new technologies. Further, as more and more enterprises use these new technologies to provide their services, the requirement for a better crawler becomes inevitable. This thesis studies the problems associated with crawling RIAs. Crawling RIAs is fundamentally more difficult than crawling traditional multi-page web applications. The thesis also presents an efficient RIA crawling strategy and compares it with existing methods.
Keywords: Web Crawling; Rich Internet Applications; Web Application Modelling